Environmental sustainability in technologically advanced economies: The role of eco-digitalization, green finance, and green technology - Maria Mazhar; Muhammad Tariq Majeed; Isma Samreen (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2025)
This study investigates the effects of eco-digitalization, green technology, and green finance on environmental sustainability in the presence of affluence and population. The sample size consists of a panel of 19 technologically advanced economies covering the time span from 1980 to 2023. The econometric model is designed using the STIRPAT framework. The empirical results are based on panel time series analysis. The panel unit root tests illustrate that variables are stationary at the first difference and follow the I (1) order of integration. The panel cointegration test confirms the presence of long-run relationships between the variables. The empirical findings reveal that eco-digitalization, green technology, and green finance help to boost environmental sustainability by reducing carbon emissions and ecological footprints in technologically advanced economies. Furthermore, the empirical investigation proceeds using two major technological phases in the sampled economies. The results reveal heterogeneous effects of technological innovations and population growth on environmental quality across the phases of technological advancement. Our findings are helpful for policymakers, environmentalists, and development practitioners in designing and implementing policies that help mitigate carbon emissions and achieve environmental sustainability.
Keywords: 330; Eco-digitalization; ICT; green technology; green finance; environmental sustainability; carbon emissions; ecological footprint